A CONSTRUÇÃO DO PROJETO POLITICO-PEDAGÓGICO DAS ESCOLAS DO CAMPO: contribuições teórico-práticas para a realidade maranhense - Macedo, Marinalva Sousa (2013)
This paper deals with the process of elaboration / implementation of public policies for basic education field and reflects on the construction of Project Political basic education schools in the field, whose locus are schools in areas of agrarian reform settlements in Maranhão, conquered by the Movement of Landless Rural Workers - MST, taking as reference the experience of the School Debra Nunes. It is emphasized that the fight for public policies to the field has as a landmark achievement of the first National Educators Educators and Agrarian Reform - I Enera, reaffirmed in I and II National Conferences For the Basic Education Field, which had the purpose to fight for quality public education to people peasants. Thus, it is possible to recognize that social movements fighting for public policy for the rural population have been able to advance in different fronts, the achievements in the formulation of regulatory frameworks and legal instruments in order to ensure Education Field. The desire for this research arose from my participation as a teacher in II Project Training Educators and Educators in Rural Education in the State of Maranhão. Initially, it was realized that the MST struggle was for education for the children of those who fought for land. Thus emerge the first schools in the settlements and opened discussions on education and in the field. Currently, the debate has motivated the development of research and production significantly beyond the attainment of guidelines for education in the field and conducting important events aiming to reflect on public education. On the other hand, increased the need to develop a political-pedagogical schools for basic education in the field, highlighting the importance of reflecting on education and educational project of the school who wants to field. Thus, we sought to understand the sense of fighting for public education, triggered by social movements, in particular the MST, for the construction of the PPP, limiting the study to the first decade of this century, marked by intense fighting move by public policies through social movements linked to the issue of the field. Broke up the following questions: Historically, in recent decades, has been consolidated as the struggle of rural social movements in public education? As it articulates the struggle for educational policy with the defense of the construction of PPP? What is the meaning of the struggle for public education triggered by social movements, in particular by the MST, in order to build the PPP for rural schools? In Maranhão, considering education field in settlement areas such as schools have been organizing to build PPP '. To achieve the intended objectives and aimed to answer these concerns, developed bibliographical, documentary and field. To do so, it is a dialogue with the authors investigating this object in its various determinations, including Coutinho (2009), Ribeiro (2012) Molina (2012), Taffarel (2012), Sources (2010), Vendramini (2008 ), Veiga (2010), Caldart (2004), Freitas (2011), D'Agostini (2012), Dalmagro (2010) and others, essential to sustain such analysis guided by a dialectical conception of education. This, based on the political, technical and ethical for a paradigm focused on a human, committed to social transformation, in different historical contexts of the reality of the field. This, then, is a methodological assumption contrary to current logic training, geared predominantly to the market. Based on this understanding, it is desired that this work can contribute critically to the delineation of the Political (PPP) of rural schools in Maranhão, considering that it should be built collectively, since it constitutes an instrument structuring of school identity , democratic management and teaching activities in schools field.